Protective factors in adolescent dating violence: A socio-ecological resilience systematic review - Humaira, Salsabila; Apsari, Nurliana Cipta; Taftazani, Budi Muhammad; Husna, Nurul; Nazamuddin, Aniza (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2026)
Adolescent dating violence (ADV) is a global issue that seriously impacts the psychological and social well-being of adolescents. To date, scientific literature tends to highlight risk factors, while protective factors that can prevent adolescent involvement in ADV are still limited. Therefore, this study aims to identify, classify, and analyze protective factors in previous studies on ADV in adolescents using Michael Ungar's (2011) socio-ecological resilience framework, which includes seven indicators. The study was conducted using the Systematic Literature Analysis (SLA) method, with data collected from six academic databases (SCOPUS, EBSCO, Cambridge University Press, Taylor & Francis, Sage Journals, and Google Scholar). Of the 711 initial documents, 13 eligible articles were selected for thematic analysis and classified based on Ungar's seven resilience indicators. The results showed that social support from peers, family, and teachers was the most consistent protective factor. This finding was followed by school-based interventions, including emotional intelligence, cultural attachments such as familismo (family cohesion), and meaningful communication with parents, as well as social norms that support collective action against violence. This study revealed that adolescent resilience to ADV is multidimensional and is formed through the interaction between individual capacity and their social environment. Preventive interventions should adopt a holistic approach that emphasizes strengthening support structures, promoting education about healthy relationships, and fostering cultural inclusivity. This study provides a conceptual foundation for ADV prevention policies and programs that are responsive to the socio-ecological context of adolescents.